You take that -2y over under the 3y and you add them and you get 5y and then u say 8+5y=-2 and then you bring the -2 over under the 8 and you get 10 and there you have it it now is 10+5y. Hope that was helpful
This seems like a lot more work than it is, but here we go Simplifying<span>8 + -2y = 3y + -2 Reorder the terms: 8 + -2y = -2 + 3y Solving 8 + -2y = -2 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 8 + -2y + -3y = -2 + 3y + -3y Combine like terms: -2y + -3y = -5y 8 + -5y = -2 + 3y + -3y Combine like terms: 3y + -3y = 0 8 + -5y = -2 + 0 8 + -5y = -2 Add '-8' to each side of the equation. 8 + -8 + -5y = -2 + -8 Combine like terms: 8 + -8 = 0 0 + -5y = -2 + -8 -5y = -2 + -8 Combine like terms: -2 + -8 = -10 -5y = -10 Divide each side by '-5'. y = 2 Simplifying y = 2</span><span>